Dys-regulation of peripheral transcript levels of ecto-5’-nucleotidase in multiple sclerosis patients - Kobarfard, Farzad; Noroozi, Rezvan; Beirami, Amirreza Dowlati; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Human antibodies, 2019)
CD73, also entitled as ecto-5 ′ -nucleotidase (NT5E), is an ecto-nucleotidase that contributes in the breakage of extracellular ATP to adenosine and the preservation of immune balance. In spite of acknowledged role for immune response imbalance in the pathogenesis of multiple sclerosis (MS), data regarding NT5E expression in MS patients are scarce. In the current study, we assessed expression of NT5E in peripheral blood of MS patients and healthy subjects to unravel its role in the pathogenesis of MS. Results of Multilevel Bayesian model showed no significant difference in NT5E expression between total MS patients and healthy subjects. However, its expression was significantly lower in male MS patients compared with male controls ( P = 0.031, 95% credible intervals: [ - 6.93, - 0.56]). No significant correlation was found between expression of NT5E and age in any study subgroups. Remarkably, NT5E transcript levels had 92.31% sensitivity and 80% specificity in diagnosis of MS disease. The diagnostic power of NT5E transcripts was 86.2% based on AUC values. Consequently, the current study indicates the role of NT5E in the pathogenesis of MS disease in male subjects. Moreover, expression level of this gene might be used as a putative marker especially in male MS patients.